First international symposium sciences and practices in swimming (Atlantica, 2006)
The book contains the (main) reports from the First international symposium science and practice in swimming held in 2005 by the French swimming federation FFN. The symposium was assessed an "enormous success". With this book FFN wants to provide a unique source of information for scientists and coaches.